CSC401 - Fundamentals of Computer Science / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
This course is an introductory course in computer science curriculum and to provide foundation skills in subsequent subjects. The course will provide an overview of components and process within a computer system. The goal is to help students understand the organization and function of components in a computer system and used the knowledge in circuit theories to solve problems concerning data transfer and control.